A digital library for health sciences educators: the health education assets library (heal) - McIntyre, Sandra A.; Dennis, Sharon E.; Uijtdehaage, Sebastian H. J.; Candler, Chris S. (Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries, 2004)
Health sciences educators have the need but neither the time nor the resources to create and index digital multimedia materials suitable for use in educational settings. The primary mission of the Health Education Assets Library (HEAL) is to address this need by providing health sciences educators with free access over the Internet to high--quality multimedia materials, including such items as images, videos, and animations The project team is working with other organizations to establish an international network of distributed databases containing high--quality teaching resources in a variety of health sciences--related subject areas HEAL's resources are freely available on the Web for use by health sciences faculty, students, and staff, as well as patients and their families. The digital library includes interfaces for searching, downloading, contributing, and browsing through materials. A custom metadata schema based on the Educause Instructional Management Systems (IMS) standard has been extended by HEAL to include additional health sciences--related elements Intellectual property issues are handled through the use of the Creative Commons set of licenses; most commonly, contributors grant free use of the library's resources for non--commercial purposes with clear attribution. The HEAL project has attracted the interest of over sixty organizational and individual partners, and by February 2004 there were over 4000 registered users. The collection is growing as new partner collections are being added by the end of late 2004, the national multimedia repository/referatory created by the HEAL team at www.healcentral.org will offer health sciences educators access to a large, diverse collection of health science materials appropriate for use in a variety of educational settings.